The Role of Civics Education in Establishing the Critical Thinking and Humanist Citizens at Universitas Muhammadiyah Semarang - arum ambarsari (Universitas Muhammadiyah Semarang, 2023)
This research determined the civics education role in establishing and realizing humanist citizens. Humanist citizens refer to citizens with values as humans in daily life behaviors and to humanize other individuals. This literature study analyzed various theories about civics and the roles of civics education in Indonesia in creating humanist citizens. Humanist citizens are the results of the expected learning outcomes after receiving civics learning in Indonesia. With civics education for primary all educational levels, such as Primary School, Junior high School, and Senior High School levels, learners will be aware of the primary values of citizens in community life. Thus, the objective of civics education is to realize humanist citizens.